2007
DOI: 10.2340/16501977-0029
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity and satisfaction in men with traumatic spinal cord lesion

Abstract: This study confirms the earlier findings that the ability to reach orgasm is deficient in men with spinal cord lesion. The completeness of the lesion had no effect. The more severe locomotory disability might adversely affect the sex life of persons with tetraplegia compared with those with paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 18 publications
3
42
1
9
Order By: Relevance
“…14 The sexual satisfaction of SA Korean men in this study was relatively lower than that of other reports in Western countries. The research of Dahlberg et al 11 reported that 36% (n = 33) of their study subjects were very or somewhat satisfied with their sexual life. Berkman et al 15 assessed the sex lives of 104 male SCI veterans and found that 41%, 36% and 23% had satisfactory, somewhat satisfactory and Table 3 Comparison of sexually active groups for sexual satisfaction unsatisfactory sex lives, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The sexual satisfaction of SA Korean men in this study was relatively lower than that of other reports in Western countries. The research of Dahlberg et al 11 reported that 36% (n = 33) of their study subjects were very or somewhat satisfied with their sexual life. Berkman et al 15 assessed the sex lives of 104 male SCI veterans and found that 41%, 36% and 23% had satisfactory, somewhat satisfactory and Table 3 Comparison of sexually active groups for sexual satisfaction unsatisfactory sex lives, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sösteen et al 9 and Reitz et al 10 reported 64% (60 males) and 60% (47 males) with SCI had had intercourse, respectively. Additionally, Dahlberg et al 11 reported that 68% of 92 males with traumatic SCI had engaged in sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…En önemli faktörler, erektil disfonksiyon ve bozulmuş ejakülasyon olarak rapor edilmiştir (14). Yaralanma sonrası ilişkiye girme oranları %57-76 aralığında bildirilmiştir (4,9,15). Yaralanma öncesi hastalarımızın %84'ü seksüel ilişkiye girmişken, bu oran yaralanma sonrası %45 idi.…”
Section: Discussionunclassified
“…Spinal kord yaralanmalı erkeklerde seksüel fonksiyonlar somatik ve otonomik sinirlerdeki hasar nedeni ile sıklıkla bozulmuştur (1,2). Ereksiyon, ejakülasyon, orgazm, fertilite ve çok çeşitli problemleri içeren seksüel fonksiyon bozukluğu lezyonun derecesine ve lokalizasyonuna göre değişir (3,4).…”
Section: Introductionunclassified
“…Another study showed that 76% of the males reported having sexual relations since the SCI and that a total of 68% had been sexually active during the last 12 months. 22 Although most participants had an active sex life, studies show that the sexual frequency diminishes after the SCI. 13,[26][27][28][29] Another study shows two motives in particular that reduce sexual frequency: physical limitations and reduction in sexual ability.…”
Section: Discussionmentioning
confidence: 99%